OPTIMALISASI PENAGIHAN PAJAK BARANG DAN JASA TERTENTU ATAS PERHOTELAN DAN MAKANAN DAN/ ATAU MINUMAN DI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA YOGYAKARTA - Nurul Amalia Hartono; Lilik Ambarwati (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to identify the challenges encountered in the collection of PBJT (Tax on Services for Hotel, Food, and/or Beverages) and to examine the efforts made by the Regional Financial and Asset Management Agency (BPKAD) to optimize tax collection. The researcher employed data triangulation as an analytical method to process both primary and secondary data obtained through interviews and observations. The findings indicate that challenges arise from both taxpayers and internal factors within BPKAD Yogyakarta City. Challenges on the taxpayers' side involve issues such as incomplete taxpayer data, low compliance, and limited financial capacity. Internal obstacles within BPKAD include limited tax collection personnel, lack of integration in the taxation information system, the ineffectiveness of forced collection letters, weak administrative sanctions, and negative perceptions of tax relief or amnesty policies. The efforts made to address these issues include direct engagement through the Regional Tax Week initiative, enhanced inter-agency cooperation, ongoing public outreach, service innovation in tax payments, integration of internal data systems, enforcement actions against non-compliant taxpayers, implementation of administrative sanctions, and the development of digital-based tax collection technology.